THE WAYS OF DEVELOPING STUDENTS’ POSITIVE HABITS OF LEARNING INDEPENDENTLY - Yaxshiboyeva , Sarafroz Komiljon qizi; Suleymanov , T.Kh (Educational Research in Universal Sciences, 2023)
This article discusses effective ways of developing students’ positive habits of learning independently. It emphasizes the importance of teaching learning skills, encouraging self-reflection, providing feedback, fostering curiosity, and using technology to support independent learning. By implementing these strategies, students can take ownership of their learning, develop critical thinking skills, and become self-directed learners. Ultimately, developing positive habits of learning independently is crucial for students’ academic success and lifelong learning.